Earth Day and the environmental movement : standing up for Earth - Peterson, Christy (Twenty-First Century Books, 2020)
Discusses the establishment of Earth Day in 1970, to protect Earth's land, air, and water, and its development over time. Includes information about Earth Day symbols, festivals, and the creation of the Environmental Protection Agency. Also features a glossary of terms, photographs, and tips for young activists.